Pharmacokinetic/pharmacodynamic (PK/PD) simulation for dosage optimization of colistin and sitafloxacin, alone and in combination, against carbapenem-, multidrug-, and colistin-resistant Acinetobacter baumannii - Rodjun, Vipavee; Montakantikul, Preecha; Houngsaitong, Jantana; Jitaree, Kamonchanok; Nosoongnoen, Wichit (Frontiers in Microbiology, 2023)
To our knowledge, no study has investigated the optimal dosage regimens of either colistin or sitafloxacin against drug-resistant Acinetobacter baumannii (A. baumannii) infections by using specific parameters. Our aim was to explore the optimal dosage regimens of colistin and sitafloxacin, either in monotherapy or in combination therapy, for the treatment of carbapenem-, multidrug-, and colistin-resistant A. baumannii infections. A Monte Carlo simulation was conducted to determine the dosage regimen that achieved the optimal probability of target attainment (PTA) and cumulative fraction of response (CFR) (≥90%) based on the specific parameters of each agent and the minimal inhibitory concentration (MIC) of the clinical isolates. This study explored the dosage regimen for patients with creatinine clearance (CrCL) of 90, 50, 30, and 10 mL/min. We can explore the dosage regimen for each CrCL for the combination therapy because higher possibility to reach the desired PTA or CFR. Focusing on the MIC90 of each agent in combination therapy, the dosage regimen for colistin was a loading dose of 300 mg followed by a maintenance dose ranging from 50 mg every 48 h to 225 mg every 12 h. The dosage regimen for sitafloxacin was 325 mg every 48 h to 750 mg every 12 h. We concluded that a lower dose than usual of colistin that based on the specific pharmacokinetic data and a higher dose than usual of sitafloxacin in combination could be an option for the treatment of carbapenem-resistant, multidrug-resistant, and colistin-resistant A. baumannii. The lower dose of colistin might show a low chance of adverse reaction, while the high dose sitafloxacin should be considered. This study tried to find more chance of the drug selection to against the crucial drug-resistant pathogen infections problem in the lack of new antibiotics situation. However, further study is needed to confirm the results of this simulation study.